Development and Application of Artificial Neural Network - Wu, Yu-chen; Feng, Jun-wen (Wireless personal communications, 2018)
Artificial neural network is a very important part in the new industry of artificial intelligence. In China, there are many researches on artificial neural network and artificial intelligence are developing rapidly. Therefore, this paper reviews and summarizes artificial neural network, and hopes that readers can get a deeper understanding of artificial neural network. This paper first reviews the development history of artificial neural network and its related theory, and introduces four major characteristics of artificial neural network, such as the non-linear, non-limitative, non-qualitative and non-convex. Then it emphatically analyzes its application in information, medicine, economy, control, transportation and psychology. Finally, the future development trend of artificial neural network is prospected and summarized.